Analisis Pelaksanaan Fungsi DPRD dalam Pembentukan Peraturan Daerah Provinsi Sumatera Utara Periode 2019-2024 - Fredy Gomgom Hutabarat; Heri Kusmanto; Tengku Irmayani (Mahesa Research Center, 2025)
This study analyzes the implementation of the legislative function of the North Sumatra Provincial DPRD in the formation of regional regulations (Perda) for the 2019-2024 period. The DPRD has a strategic role in producing regional regulations, but of the 72 Ranperda proposed, only 30 were passed (42%), showing that productivity is still low compared to other provinces. This study uses a qualitative approach with a descriptive method. The data was obtained through in-depth interviews with members of the DPRD, executive officials, and other stakeholders, as well as analysis of related documents. The theories used include the Theory of Deliberative Democracy (Habermas), as well as the Theory of Risk Society and Risk Modernity (Beck and Giddens), to understand the dynamics of legislation and the relevance of the resulting regulations. The results of the study show that the low productivity of the DPRD in the formation of the Regional Regulation is caused by several main factors, namely the long and complex drafting process, the density of the work agenda of the DPRD members, and the low participation of the community in policy formulation. In addition, the quality and relevance of the resulting Regional Regulations still need to be improved so that they can be more effective in answering the needs of the people of North Sumatra. This study recommends strengthening the deliberation mechanism, optimizing the legislative function of the DPRD, and increasing public participation so that the resulting policies are more representative and of higher quality.